Ozone and anions generator for disinfection of enclosed spaces. Issue 1 (February 2021) - Popa, G N; Popa, L; Diniş, C M
Abstract: After the pandemic of SARS-CoV-2, people's lives will be different. It seems that in the next period, due to the spread of SARS-CoV-2 virus worldwide, all objects, surfaces and spaces that people come in contact with must be disinfected frequently. At the same time, the atmosphere in closed spaces must be disinfected because the transmission of the virus through the air is made easier. It seems that an effective method of disinfection (viruses, bacteria, etc.) is the use of ozone generators. Ozone in the air over a certain dose affects the human respiratory system. It is known the role of anions on human health, especially given that the vast majority will spend time indoors. Staying in homes for long periods of time has negative effects on the humans body. The paper presents and analyze ozone, anions, and the their generators. It is presented a generator that can produce both ozone (measured with an electrochemical sensor) at a certain concentration for limited periods of time, as well as anions in high concentrations that have a beneficial effect on humans health. Air quality is measured (with an electrochemical sensor), and in conditions of low quality, the generator can provide higher concentrations of anions. The ozone and anions generator is controlled with microcontroller development board. The flowchart of the program used in the microcontroller is presented.